Relativity in fundamental astronomy : dynamics, reference frames, and data analysis : proceedings of the 261st Symposium of the International Astronomical Union held in Virginia Beach, Virginia, USA : April 27-May 1, 2009 - International Astronomical Union. Symposium 2009 : Virginia Beach, Va.); Klioner, Sergei A.; Seidelmann, P. Kenneth; Soffel, Michael H., 1953- (Cambridge ; Cambridge University Press, 2010)
"General relativity provides our best description of gravitation in modern physics - currently all observations and tests of gravitational theories have agreed with it. GR is applied in fields as diverse as fundamental astronomy, astrophysics, geodesy, physics, and space sciences, where high-accuracy observations and measurements are taken or modeled. IAU Symposium 261 summarizes the present state of applied relativity. It considers the applications of general relativity in a wide range of disciplines: geodesy, navigation, solar system ephemerides, space missions, pulsar timing, high-accuracy astrometry, gravity waves, gravitational lenses, and black hole astrophysics. The future tests of general relativity based on improved observational accuracies and higher order developments of the theory are discussed in general. Specific projects designed to test the theory in the near future are also covered. This volume is a useful resource for all those interested in general and special relativity, their current applications and future tests." -- Publisher's description.
Preface -- 1. Astronomical space-time reference frames -- 2. Astronomical constants, nomenclature and units of measurement -- 3. Time scales, clock and time transfer -- 4. Equations of motion of astronomical bodies and light rays -- 5. Motion of astronomical bodies -- 6. Experimental foundations of general relativity -- 7. Pulsar timing -- 8. Astrometric and timing signatures of gravitational lensing and gravity waves -- 9. Astrometric and timing signatures of galactic and extragalactic black holes -- 10. Astrometry and ground-based interferometry -- 11. Promises and challenges of Gaia -- 12. Future high-accuracy projects -- 13. Future prospects of testing general relativity.
Includes bibliographical references and indexes.
Keywords: Relativity (Physics) -- Congresses; Astronomy -- Congresses